Pelaksanaan Pembinaan Disiplin Peserta Didik Dalam Proses Pembelajaran - Ibrahim Ibrahim; Tazkia Nabila; Nisa Rahmaliya; Kris Setyaningsih (Universitas Maritim AMNI Semarang, 2023)
One of the things that greatly influences students' learning is discipline, which is a condition where students show attitudes, appearances, and behaviors that are in accordance with the rules, values, norms, and provisions that apply in schools, classes, or wherever students are. The purpose of this study is to review the literature on ways to foster student discipline in learning activities. This study uses the Literature Review method. Data were collected by documenting and reviewing all articles related to student discipline development that have similarities with this report. The results of the literature review show that student discipline development can be done by making school rules and introducing the school environment, as well as by using self-control techniques, external control, and cooperative control. Evaluation of discipline development is carried out at the end of each academic year by reporting the results of the discipline development program in terms of attendance and achievement of KKM in the report book. This discipline development has a positive impact on students in learning activities.